Impaired Discrimination with Intact Crossmodal Association in Aged Rats: A Dissociation of Perirhinal Cortical-Dependent Behaviors - Gaynor, Leslie S. (Behav Neurosci, 2018)
The perirhinal cortex (PRC) supports associative memory and perception, and PRC dysfunction impairs animals’ abilities to associate stimulus features across sensory modalities. PRC damage also leads to deficits in discriminating between stimuli that share features. While PRC-dependent stimulus discrimination has been shown to be impaired with advanced age, data regarding the abilities of older adults and other animals to form PRC-dependent associations have been equivocal. Moreover, the extent to which similar neural computations within the PRC support associative memory versus discrimination abilities have not been directly examined. In the current study, young and aged rats were cross-characterized on two PRC-dependent crossmodal object recognition (CMOR) tasks to test associative memory, and a LEGO® object discrimination task. In the CMOR tasks, rats were familiarized with an object with access to tactile input and then tested for recognition with visual input only. The relative exploration time of novel versus familiar objects indicated that aged rats showed preference for the novel over familiar object with and without an epoch of multimodal pre-exposure to the familiar object prior to the testing session. Furthermore, crossmodal recognition performance between young and aged rats was not significantly different. In contrast, for the LEGO object discrimination task, aged rats were impaired relative to young. Notably, aged rats who performed poorly on the LEGO object discrimination task had better performance on the CMOR tasks. The dissociation of discrimination and association abilities with age suggests that these behaviors rely on distinct neural computations within PRC-medial temporal lobe circuit.